2019
DOI: 10.1111/jpy.12831
|View full text |Cite
|
Sign up to set email alerts
|

Toward a multigene phylogeny of the Cymatosiraceae (Bacillariophyta, Mediophyceae) II: morphological and molecular insights into the taxonomy of the forgotten species Campylosira africana and of Extubocellulus, with a description of two new taxa

Abstract: New molecular and morphological insights are presented on Campylosira africana and two new species, Extubocellulus cupola sp. nov. and Plagiogrammopsis castigatus sp. nov. Species descriptions were based on LM/SEM micrographs and a data set with concatenated sequences of SSU, rbcL and psbC loci constructed from 56 cymatosiroid strains isolated from global geographic locations. Extubocellulus cupola is distinguished by a mesh‐like marginal ridge and dome‐shaped areolation, and P. castigatus, by a prominent marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Others studies showed that the presence of diatom taxa with broad tropical ranges in coral reefs of the Western Indian Ocean coasts and in the SE Pacific (Li et al 2015(Li et al , 2018). Yet Lobban et al (2012), Ashworth et al (2012), Dąbek et al (2017Dąbek et al ( , 2019, Li et al (2016Li et al ( ,2020; but see also Kryk et al, 2020) have clearly shown numerous taxa limited in their distribution to particular sites. Our analysis of the published research given above involving the use of molecular methods and identification of processed samples allowed us to distinguish three major groups of diatom taxa in terms of their biogeography: cosmopolitan species, including some adapted and also distributed in cold water areas, but rather in the Arctic and Greenland than the Southern Ocean.…”
Section: Biogeographymentioning
confidence: 98%
See 1 more Smart Citation
“…Others studies showed that the presence of diatom taxa with broad tropical ranges in coral reefs of the Western Indian Ocean coasts and in the SE Pacific (Li et al 2015(Li et al , 2018). Yet Lobban et al (2012), Ashworth et al (2012), Dąbek et al (2017Dąbek et al ( , 2019, Li et al (2016Li et al ( ,2020; but see also Kryk et al, 2020) have clearly shown numerous taxa limited in their distribution to particular sites. Our analysis of the published research given above involving the use of molecular methods and identification of processed samples allowed us to distinguish three major groups of diatom taxa in terms of their biogeography: cosmopolitan species, including some adapted and also distributed in cold water areas, but rather in the Arctic and Greenland than the Southern Ocean.…”
Section: Biogeographymentioning
confidence: 98%
“…Gottschalk et al, 2007;Hein et al, 2008;Lobban et al, 2012;Desrosiers, 2014;Al Handal et al, 2016;Kryk et al, 2020). Many species and genera have been described based on monoclonal strains and molecular markers have been acquired (Sato, 2008;Ashworth et al, 2012;MacGillivary & Kaczmarska 2012Lobban and Ashworth, 2014;Li et al 2016Li et al , 2018Dąbek et al 2017Dąbek et al , 2019Prasetiya et al, 2019;Witkowski et al, 2020).…”
mentioning
confidence: 99%
“…Strain SZCZM1454A, morphologically identified as Halamphora cf. salinicola, has been isolated from the water sample originating from Köyce giz Lake, Dalyan Channel in Turkey (36 • 50 34.4" N, 28 • 37 54.6" E), using micropipette technique under the inverted LM described in [25,26]. The diatom was grown in Petri dish enriched with artificial f/2 culture medium [27] with salinity adjusted to 35‰ and kept in a plant growth chamber (FITO1400i, Biogenet, Poland) with a 12:12-h light:dark photoperiod at 20 • C and illuminated with ca.…”
Section: Diatom Isolation and Culturementioning
confidence: 99%
“…10 days. A subsample of the clonal culture biomass was then cleaned and boiled with 37% hydrogen peroxide and microscopic slides were prepared as described in Dąbek et al, 2017;Dąbek et al, 2019). Cleaned material of H. ostrearia (voucher strain no.…”
Section: Sampling and Sample Preparationmentioning
confidence: 99%
“…The 'Golden era' in South African marine diatomology was associated with the research of Professor Malcolm Giffen (1902Giffen ( -1986, who produced numerous papers on marine and estuarine benthic diatoms of the Indian Ocean, south coast in the Eastern Cape Province (Giffen, 1963;Giffen, 1966;Giffen, 1970a) and the Atlantic Ocean, west coast between Gordon's Bay and Namaqualand (Giffen, 1970b;Giffen, 1971;Giffen, 1973;Giffen, 1975;Giffen, 1976;Giffen, 1984). More recently, marine benthic diatom research was focused on taxonomy and phylogeny (e.g., Dąbek et al, 2013;Dąbek et al, 2014;Dąbek et al, 2019), local diversity and ecology (Cotiyane-Pondo et al, 2020;Cotiyane-Pondo and Bornman, 2021a;Cotiyane-Pondo et al, 2021b) or epiphytic, epibiontic host-diatoms relationships (Majewska et al, 2019a;Majewska et al, 2019b;Majewska, 2020;Mayombo et al, 2020;Majewska et al, 2022).…”
Section: Introductionmentioning
confidence: 99%